Pendampingan Administrasi Perpajakan dan Literasi Layanan Digital DJP melalui Program KKN-Profesi di KPP Pratama Makassar Selatan - Lestari, Andi Indah; Fadrianti, Reza (Journal Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Community service through the Professional Community Services Program (KKN-Profesi) is an implementation of the Tri Dharma of Higher Education aimed at strengthening collaboration between academic institutions and public service organizations. This program was conducted at KPP Pratama Makassar Selatan, a technical unit of the Directorate General of Taxes under the Ministry of Finance of the Republic of Indonesia. The program aimed to support tax administrative services, improve administrative efficiency, and enhance taxpayers’ digital tax literacy. The methods employed included administrative assistance, document archiving and digitalization, taxpayer assistance in utilizing digital tax services, and participation in tax education activities. The results indicate that the program contributed to improved administrative efficiency, more systematic document management, and increased taxpayers’ understanding of digital tax services.